2019
DOI: 10.3390/su11164406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sustainability and Technology Orientations on Firm Growth: Evidence from Chinese Manufacturing

Abstract: Prior literature from a cognitive perspective analyzing the effects of different content and structure of managerial cognition on sustainability are lacking. This study attempts to fill this gap by examining the relationship between technology orientation, sustainability orientation, and firm growth. Sustainability development has received unprecedented attention in the 12th five-year plan of China, who is the world’s largest energy consumer. This study tested the model of Chinese manufacturing in the year whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 71 publications
4
11
0
Order By: Relevance
“…By cultivating interest in the knowledge of consumers and rivals, market-based companies can effectively adapt and respond to evolving consumer demands by providing new goods and services (Ali et al, 2020). Technology orientation also exhibits a significant effect on the performance of SMEs (β = 0.211, t = 3.009, p < 0.05), supporting the results of Hsu et al (2014) and Lei et al (2019). Therefore, technology orientation may encourage risk-taking, create innovative ideas that shape consumer behaviour and contribute to the growth of developing markets (Ali et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…By cultivating interest in the knowledge of consumers and rivals, market-based companies can effectively adapt and respond to evolving consumer demands by providing new goods and services (Ali et al, 2020). Technology orientation also exhibits a significant effect on the performance of SMEs (β = 0.211, t = 3.009, p < 0.05), supporting the results of Hsu et al (2014) and Lei et al (2019). Therefore, technology orientation may encourage risk-taking, create innovative ideas that shape consumer behaviour and contribute to the growth of developing markets (Ali et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…Gatignon and Xuereb (1997) have described technology orientation as being able and committed to obtaining and using considerable technical experience in innovative technologies. Lei et al (2019) also described technology orientation as the company ability to suggest or incorporate new technology, products or inventions. This description implies that the importance of consumers and longterm enterprise performance rely on the introduction of innovative technical solutions, goods, facilities or procedures (Kumar et al, 2018).…”
Section: Strategic Orientation (So)mentioning
confidence: 99%
“…Sivathanu and Pillai (2019) suggested that SO does not significantly affect the SEP in a resource-constrained developing country context, but EO and TO significantly influence sustainable entrepreneurship (SE). Moreover, Lei et al (2019) found a positive association of SO and TO with firm growth. In addition, these authors further suggest that in fast-growing industries, firms with a high sustainability orientation had lower levels of firm growth to some extent.…”
Section: Interrelationshipsmentioning
confidence: 90%
“…More than 50% of total studies included in this review investigated the firm-level outcomes of deploying sustainability orientation. On the other hand, some recent studies have extended this debate and reported that the positive association between sustainability orientation and firm performance is negatively moderated by sustainability decision tradeoffs (Kautonen et al, 2020) and industry growth (Lei et al, 2019). There also exists some empirical evidence that suggests its negative association with sustainable entrepreneurship (Sivathanu & Pillai, 2019) and entrepreneurial bricolage (Hooi, Ahmad, Amran, & Rahman, 2016).…”
Section: Meso (Organizational Level)mentioning
confidence: 99%
See 1 more Smart Citation